Let G be a group. Prove that G is abelian if and only if (ab)^-1 = a^-1 * b^-1 for all a,b in G.

Printable View

- Oct 8th 2009, 06:38 PMelninioProve G is abelian iff...
Let G be a group. Prove that G is abelian if and only if (ab)^-1 = a^-1 * b^-1 for all a,b in G.

- Oct 8th 2009, 08:49 PMGamma
First note we always have $\displaystyle (ab)^{-1}=b^{-1}a^{-1}$ See why?

so if G is abelian, the forward direction is clear (just move them past eachother). Conversely, if we have $\displaystyle a^{-1}b^{-1}=(ab)^{-1}=b^{-1}a^{-1}$ for all a and b in G.

Just multiply on the left by (ba) and on the right by (ab)